Use of shear thickening fluids in sport protection applications: a review - Parisi, Mariafederica; La Fauci, Giuseppe; Pugno, Nicola M.; Colonna, Martino (Frontiers in Materials, 2023)
Nowadays, safety devices (e.g. helmets, safety barriers, body protectors etc) producers are developing and testing innovative smart materials to reach the ever-growing request for higher performances arising from international standards and markets. Shear thickening fluids (STFs) have attracted special attention because of their non-linear mechanical response and high-energy dissipation effectiveness. In particular, within STF, shear thickening gels (STGs), a class of high-molecular-weight and crosslinked polymers have exhibited great stability and shear-dependent properties ascribable to the presence of dynamic boron-oxygen crosslinks within the polymeric structure. Hence, it is essential to investigate the rheological behavior of these system for their application in new flexible and impact protection devices. This review focuses on the description of the peculiar advantages of using STFs with regards to traditional materials in sport protective equipment. Moreover, the preparation and use of STFs for impact protection including all the scientific productions and the conspicuous patent literature on this field -from dilatant suspension until the latest STGshave been reviewed in detail. Commercial helmets and body protectors containing STFs have also been reviewed and reported. Finally, the use of STGs not embedded in foams in sport helmet is also discussed and a final part on future perspective of STFs for sport protection is provided.